2016
DOI: 10.5812/archcid.28973
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Etiologies and Antibiotic Susceptibility Pattern of Urinary Tract Infections at the Pediatric Ward of Dastgheib Hospital, Shiraz, Iran: A Three-Year Study (2009 - 2011)

Abstract: Background: Urinary tract infection (UTI) is one of the most common infections in children. Timely diagnosis and appropriate treatment of UTI requires knowledge of etiologic agents and antibiotic resistance pattern of common uropathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Our results were consistent with other studies that showed that UTI was more frequent in females [ 5 , 13 , 15 , 16 ]. High frequency of UTI in females can be due to anatomical differences such as shortness of urethra and close space between the anus and urethral orifice [ 17 , 18 ]. However, some studies reported that UTI at an early age (<2 years) is greater in boys than that in girls [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results were consistent with other studies that showed that UTI was more frequent in females [ 5 , 13 , 15 , 16 ]. High frequency of UTI in females can be due to anatomical differences such as shortness of urethra and close space between the anus and urethral orifice [ 17 , 18 ]. However, some studies reported that UTI at an early age (<2 years) is greater in boys than that in girls [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 63% of the enrolled cases were male ( P =0.030), and no significant difference was observed in the incidence rate of UTI in the male and female in the UTI cases. Nevertheless, most of the studies on pediatric UTI indicate that the incidence of UTI in females is more than in males, other than the neonatal group ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Variation exist between patterns of sensitivity and resistance regarding different microorganisms and antibiotics in different regions of the world so it is always advisable to keep up to date with the recent trends. 5,6 A study found sensitivity of ceftriaxone as 44.5%, ciprofloxacin 32.7%, gentamycin 45.5% and ofloxacin 24.5% in children with UTIs. 7 While results of urine culture and sensitivity is awaited, treating suspected children with UTI adopting empirical antibiotic treatment is a usual management practice.…”
mentioning
confidence: 99%